Efektivitas Program Back School Dan Teknik Mckenzie Pada Pasien Nyeri Punggung Bawah - Saifudin Zuhri; Marti Rustanti (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Back School Program, Mckenzie Techniques, Pain, Vas, Patients With Low Back Pain. On the other hand needed McKenzie method for relaxation to the muscles of the back due to spasm, so that the pain can be reduced. To prove the effectiveness of the program back school and McKenzie techniques in reducing lower back pain. Types of Research: experimental study. Two group pre test-post test design. Place and Time Research in Unit physiotherapy Hospital Dr Moewardi Surakarta from January to June 2015. Sample: lower back pain patients who met the study criteria. Research variables: independent variable is a back school program and McKenzie techniques, while the dependent variable was pain. The research data in the form of pain measured by VAS. Data obtained include scale ratio. Statistical Analysis: The subjects in one group <30 people, then analyzed with nonparametric tests. Homogeneity of data were tested with the Mann-Whitney test was obtained p = 0.030 (P <0.05) indicates the data are not homogeneous. Wilcoxon test group I obtained p = 0.000 (p <0.05) showed no difference effect of back school programs to decrease lower back pain. Wilcoxon test group II obtained p = 0.000 (p <0.05) showed no difference effect of McKenzie technique to decrease lower back pain. Mann-Whitney test after treatment was obtained p = 0.006 (p <0.05) showed no difference in effectiveness between the back school program with McKenzie techniques in reducing lower back pain. Results of the mean difference in pain reduction anatara back school program with the technique gained 9.71 higher McKenzie Techniques. McKenzie Technique is more effective than a back school program to reduce lower back pain.